2019
DOI: 10.1002/pits.22328
|View full text |Cite
|
Sign up to set email alerts
|

The assessment needs of families with children who are deaf and hard of hearing referred for an autism spectrum disorder evaluation

Abstract: With the increasing prevalence of autism spectrum disorder (ASD), clinicians and schools are receiving a larger number of assessment referrals for eligibility or diagnostic clarification of ASD in children who are deaf and hard of hearing (D/HH).Meeting this increasing demand is often difficult given not all assessment professionals seek specialized ASD training and even fewer have experience working with D/HH children.Therefore, families are disadvantaged because of the lack of assessment professionals who sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Denmark (2011) stated that the Autism Diagnostic Observation Schedule-Generic (ADOS-G) was the only assessment for ASD in deaf children. However, Dale and Neild (2020) noted, "The ADOS-2, however, falls in line with most standardized assessments in its lack of standardization with the deaf and hard of hearing (D/HH) population. The validation sample of the ADOS-2 did not include individuals who were D/HH" (p. 477).…”
Section: Diagnosing Asd In Deaf Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…Denmark (2011) stated that the Autism Diagnostic Observation Schedule-Generic (ADOS-G) was the only assessment for ASD in deaf children. However, Dale and Neild (2020) noted, "The ADOS-2, however, falls in line with most standardized assessments in its lack of standardization with the deaf and hard of hearing (D/HH) population. The validation sample of the ADOS-2 did not include individuals who were D/HH" (p. 477).…”
Section: Diagnosing Asd In Deaf Childrenmentioning
confidence: 99%
“…Therefore, there is no standardized psychometrically validated assessment for diagnosing these conditions, and the ADOS-2 is inappropriate for deaf children (Dale & Neild, 2020). When autism is diagnosed late in deaf children, it makes it more difficult for parents and educators to distinguish the characteristics of deafness from those of autism (Szarkowski & Johnston, 2018) whilst also limiting the resources available for parents and teachers to identify autism and deafness (Dale & Neild, 2020;Szarkowski & Johnston, 2018;Szymanski & Brice, 2008). Szymanski and Brice (2008) demonstrated that the characteristics of autism can appear similar to a loss of hearing ability, and vice versa.…”
Section: Diagnosing Asd In Deaf Childrenmentioning
confidence: 99%
See 2 more Smart Citations